Oligomerization of Fischer-Tropsch Olefins by Radical Initiation Method for Synthesizing Poly Olefin Base Oils - Kataria, Yash Vijay; Kashparova, Vera P.; Klushin, Victor А.; Papeta, Olga P.; Yakovenko, Roman E.; Zubkov, Ivan N. (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
In the present work we have investigated the oligomerization process of Fischer-Tropsch synthesis products – gasoline (C5-C10) and diesel (C11-C18) hydrocarbon fractions with a total olefin content (consisting mainly olefins with a branched isomeric chain) of 79.3 and 31.8 wt.%, respectively. Oligomerization was carried out by radical initiation method using azobisisobutyronitrile, benzoyl peroxide, dicumyl peroxide and methyl ethyl ketone peroxide (Butanox M-50) as initiators. It was established that the yield of the oligomerization process depending on the initiator used decreases in the following order: azobisisobutyronitrile > benzoyl peroxide > dicumyl peroxide > Butanox M-50. It was determined that when the oligomerization is carried out in polar solvents such as acetone and dichloromethane the yield of product increases by ~2.1 and ~1.7 times, respectively, while at the same time adding a non-polar solvent such as tetrachloromethane to the reaction mixture decreases the product yield by ~2.0 times. The optimal technological parameters for carrying out oligomerization process of synthetic gasoline and diesel fractions were determined: where azobisisobutyronitrile, content 0.5 wt.%., is used as an initiator, acetone as solvent, with reaction temperature of 200 °C, and duration of 12 hrs. under inert atmosphere. The product yield from the diesel fraction is 39.5 %, and from the synthetic gasoline fraction – 36.0 %. At the same time, in terms of characteristics, the oligomerization product of the diesel fraction showed properties similar to commercially available Base oil 3cSt (Group III), and the gasoline fraction showed properties on par with the commercially produced PAO-2 (Group IV). Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).